Pemeriksaan Komposisi Tubuh dalam Upaya Deteksi Dini Normal Weight Obesity pada Usia Produktif - David Limanan; Alexander Halim Santoso; Fransiska Iriani Dewi; Jeffrey Saputra Kawi; Edwin Destra; Farell Christian Gunaidi (STIKes Ibnu Sina Ajibarang, 2025)
Normal Weight Obesity (NWO) is a condition in which an individual has a normal weight but a high body fat percentage, increasing the risk of metabolic diseases. Early detection through body composition assessments is essential to prevent health complications in individuals with normal weight but imbalanced body composition. Activities include health education, body composition assessments, and the implementation of preventive measures through healthy lifestyle changes. Assessment results indicate that some individuals have a high body fat proportion despite having a normal weight range. The education provided enhances participants' understanding of NWO risks and the importance of balanced body composition to maintain metabolic health. Body composition assessments in the productive age group enable early detection of body component imbalances not visible through weight alone. Preventive measures such as balanced nutrition and regular physical activity play a significant role in maintaining a healthy body composition and reducing the risk of NWO. Body composition assessment is an effective preventive strategy to detect NWO and promote a healthy lifestyle in the productive age group.